MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI MELALUI PERMAINAN SNAKE AND LADDER MODIFIED BOARD DI RA SUNAN KALIJOGO KALIPARE-MALANG - Windhi Lesna Dewi; Evi Nurhalimah (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2023)
Implementation of snake and ladder modified board games in improving cognitive abilities in early childhood. The aim is to get the results of the development of cognitive abilities in children. The type of research used is classroom action research (PTK) to see the cognitive abilities of children who are less than optimal. In data collection, through interviews, observation, and documentation. The results of the research and discussion developed on the Snake and Ladder Modified Board game media conducted at RA Sunan Kalijogo Kalipare show that the Snake and Ladder game in terms of modification of the form of media creation is different from snakes and ladders games in general besides being played individually or in groups. The results of a very significant increase in cognitive abilities were proven from the results of the third day percentage of 57.5% in cycle I and the results in cycle II reached 77.5% which was carried out in only one meeting. The Snake and Ladder Modified Board game has obstacles including inadequate venue size with limited media and time. Research suggestions emphasize the selection of instructional media with more emphasis on design concepts and effective and efficient utilization.